Upaya Peningkatan Produktivitas Karyawan pada PT. Mahavhira Lintas Raya - Linda Mia Ayu Lestari; Rahmat Agus Santoso; Heru Baskoro (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Background – Achieving productivity in line with expectations is one of the goals of every company, if human resources are competent, have high abilities and are supported by existing technology, if this is paid attention to and prioritized, there is a big possibility that productivity in a company will not decline. Objective - This research aims to find out what causes the decline in productivity and then what efforts have been made by the company to increase productivity again and also an indication of the factors that shape productivity. Design/Methodology/Approach – This type of research is qualitative research. The technique used in this research is purposive sampling. The data validity technique used in this research is member check. The data analysis techniques in this research are data collection, data reduction, data presentation and drawing conclusions. Findings - This research obtained three results, in terms of decline, namely environmental conditions, employee knowledge, and work ethic. The result of improvement efforts is appreciation from the company for its employees and also the strategies used. The result of the indication of formation is empowerment. Research Implications - This research can be used as a reference but can use different research methods and techniques and PT. It is hoped that Mahavhira Lintas Raya can pay more attention to employee capabilities, especially the technology used so that in the future something similar does not happen and can also increase productivity again in accordance with the specified targets. Research Limits - This research still has limitations, namely weaknesses and testing the validity of the data using only member checks needs to be improved to make it more credible.